Cyto-histological discrepancy: a case report of anal cytology - Silva, Andreia; Teixeira, Catarina; Seabra, Rosária; Freitas, Cristina; Ribeiro, Maria (Citotech Online - Case Review, 2017)
Anal cancer is rare but its incidence has been increasing particularly in the HIV-positive population in which HPV infection has increased persistence. Infection with high-risk HPV types is associated with the presence and progression of dysplastic lesions into anal cancer. For this reason, HIV positive population are considered a risk group, which should be referred for screening of anal lesions. In this article we report a clinical case of a 53-year-old HIV-positive man with discrepant cyto-histological diagnosis in which cytology has been diagnosing lesions of a higher grade than histology. The present work intends to alert to the importance of anal screening, especially in the risk groups and to the evaluation of discrepant diagnoses between cytology and histology.